Pembangunan Lingkungan Bahasa Arab Aktif Berbasis Komunitas di Pesantren Modern Fathul Majid Kasiman Bojonegoro - Makinuddin, Mohammad (Institut Muslim Cendekia, 2025)
This study is motivated by the importance of developing an active Arabic language environment in pesantren as an effective and sustainable effort to improve students’ oral and written communication skills. The purpose of this research is to reveal a strategic model for building an active Arabic language environment based on community at Pesantren Modern Fathul Majid Kasiman Bojonegoro and to analyze the challenges faced in its implementation. The method used is qualitative research with data collected through in-depth interviews, systematic observations, and document studies, which are then thematically analyzed using the Community Language Learning approach and second language acquisition theory. The results show that the active language environment model, which includes tiered programs, peer mentoring, and thematic activities, effectively shapes a language habitus and enhances students’ motivation and skills. The main obstacles include limited supporting facilities and the diverse backgrounds of students affecting language adaptation. The novelty of this study lies in the integration of community management and collaborative approaches to develop a holistic and adaptive language ecosystem responsive to the needs of today’s learners, with the implication that it can serve as a model for similar educational institutions in sustainably developing second language acquisition.